IoT-based student e-attendance management system - Mohammed Idrun, Nabil Najmi; Sidik, Norbaiti; Mokhtar, Siti Musliha Ajmal; M. Zin, Nor Affida (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
An IoT-based Attendance System report using an Esp-32 microcontroller reveals an ultrasonic sensor, RFID reader, and fingerprint sensor integration. The ultrasonic sensor on the other hand picks out a person's presence to start the system so that energy conservation is honored by activating only one component at a time when the load demands it. The user verifies / authenticates the ID cards using the RFID reader, and the fingerprint sensor provides biometric verification. An LED screen displays user IDs, authentication status, and other relevant information in real-time. A Wi-Fi module is used to transfer live data to a central server for remote monitoring and control, and the attendance register is saved in an external module storage. The Proteus simulation platform, through which the system is developed, flexibly collects and processes sensor data as a means to control attendance. Beside ultrasonic activation as well, card authentication and biometric verification, are all combined to provide more advanced level security measures, reliability, and give the infrastructure efficient power consumption in the attendance management area.